Automação residencial utilizando conceitos de IoT focado em eficiência energética - QUEIROZ, Matheus Castelo Branco (2018)
This paper presents the development of a project that encompasses the concepts of Residential Automation, Internet of Things and Energy Efficiency. It is a robust system with a low implementation cost. Using recent technologies, a system has been created that allows the end user to remotely access their home sockets, verifying their consumption in real time and if there is any equipment connected at each outlet. The system also enables the user to remotely turn the outlets on or off. The system has three main components: Hardware, built using an ESP8266 microcontroller, an ACS712 current sensor and a relay module; the embedded software developed using the Arduino IDE; and the Website, developed using HTML, CSS and Javascript technologies. In addition, the MQTT protocol was used to send and receive data between these parts. Throughout this work the main concepts that were used during the development of this project are explained, the hardware and software resources used are described individually, as well as the development of the project, its results and some projects that are intended to be developed based on this project.